Patients’ and nurses’ perceptions for the protection of privacy in hospitals: a comparative study - Lemonidou, Chryssoula; Panagiotou, A; Leino-Kilpi, Helena; Välimäki, Maritta; Dassen, Theo; Gasull, Maria; Scott, Philomena Anne; Arndt, Marianne; Merkouris, Anastasios (My University, 2003)
Aim: To explore and compare the elderly and surgical patients' and mothers' and the corresponding nursing personnel's perceptions about the realization of patients' privacy in Greek hospitals. Material - Method: The study was comparative and the data have been collected from a convenience sample of 678 patients (251 mothers, 275 surgical and 152 elderly patients) and 587 nurses (221, 222 and 144) from the respective wards of 27 Greek hospitals. The questionnaire consisted of 11 items asking from the respondents to rate the frequency (Likert type scale. R=l-5) of the protection of patients' privacy by the nursing personnel during the performance of specific nursing interventions. Results: A difference was found between the perceptions of patients and nurses concerning the realization of privacy with patients to believe that their privacy had been protected less frequently than the nursing staff (Mean = 2.82-3.50 respectively, P<0.001). Furthermore, surgical patients (Mean=2.36) believed that their privacy had been protected less frequently (P<0.001) than the privacy of mothers (Mean=3.11) and elderly patients (Mean=3.19). The same difference was found between surgical nurses (Mean=3.15, P<0.001) and those nurses working in maternity wards (Mean=3.75) and elderly wards (Mean=3.79). Conclusions: Nurses, especially those who work in surgical wards, must become aware of the importance of privacy and strive to protect this basic right in the every day practice.